2016
DOI: 10.1007/s10936-016-9467-6
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Competency and Obsessive–Compulsive Disorder: A Comparative Assessment with Normal Controls

Abstract: Unlike such cognitive impairments as autism and schizophrenia, the speech pattern in obsessive-compulsive disorder (OCD) has largely remained underrepresented. We examined the pragmatic competence of OCD-affected individuals under two variant modes: pragmatic recognition and pragmatic production. In the recognition phase, the informants completed a discourse completion test around two speech acts of request and apology (20 high power distance situations). The production phase was carried out through an intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
10
0
2
Order By: Relevance
“…Self-reporting of the teenagers indicated a significant improvement in their social skills with friends and parents. Parental reports, using the Social Anxiety Scale (Ghahari et al, 2017;Brown et al, 1997), showed a reduction in the social anxiety of their adolescent children. This program is one of the few that includes teacher-facilitated interventions that show efficacy in improving social skills in adolescents with ASD in the classroom, one of the most natural social contexts (White et al, 2007;Reichow & Volkmar, 2010;Laugeson et al, 2014).…”
Section: The Uclapeers Programmentioning
confidence: 98%
“…Self-reporting of the teenagers indicated a significant improvement in their social skills with friends and parents. Parental reports, using the Social Anxiety Scale (Ghahari et al, 2017;Brown et al, 1997), showed a reduction in the social anxiety of their adolescent children. This program is one of the few that includes teacher-facilitated interventions that show efficacy in improving social skills in adolescents with ASD in the classroom, one of the most natural social contexts (White et al, 2007;Reichow & Volkmar, 2010;Laugeson et al, 2014).…”
Section: The Uclapeers Programmentioning
confidence: 98%
“…Diversos estudos têm associado os resultados da intervenção às habilidades de compreensão da comunicação não verbal, uso de material lúdico e habilidades cognitivas aos resultados da intervenção (23)(24)(25)(26) . Diversos pesquisadores têm abordado temas específicos na proposição de formas de avaliar as habilidades de comunicação em crianças com TEA (27) , com outros distúrbios do desenvolvimento (28) e em desenvolvimento típico (11) . As propostas envolvem a utilização de entrevistas (18) , questionários (8) e amostras de comunicação espontânea (29) .…”
Section: Discussionunclassified
“…In the following, information about the psychometric properties of the APP scales is provided including objectivity, reliability, construct validity, and criterion validity. We report the psychometric properties for the motor, cognition, and language scale (except for the pragmatic language skills assessed by the Orion's Pragmatic Language Skills Questionnaire, Ghahari et al, 2017). The psychometric properties of THE KLEINEWELTENTDECKER APP 20 the social-emotional scales are well-documented in the respective publications mentioned above.…”
Section: Psychometric Properties Of Scalementioning
confidence: 93%
“…The following skills were implemented in the language scale: early pre-verbal, Language Skills Questionnaire (e.g., Ghahari et al, 2017), which assesses nonverbal communication, language production, conversational skills like topic maintenance and turn taking, speech conventions and peer skills in 53 items. For all morphological and syntactical skills, we created prototypical sentences in which the target morphological flexion or syntactic construction word were highlighted.…”
Section: Language Scalementioning
confidence: 99%